Alcohol use disorder and associated factors among adult women (Research, Society and Development, 2022)
The aim of this study was to estimate the prevalence of alcohol use disorder among the adult female population living in the urban area of Dourados, MS, Brazil, and to evaluate the association with socioeconomic, behavioral and health factors. This is a population-based cross-sectional study with adult women aged 20 to 59 years. The sampling was performed by clusters in multiple stages. Alcohol use disorder was assessed from the Alcohol Use Disorder Identification Test (AUDIT), being positive when 8 or higher. The statistical analysis of the information was performed by the Chi-square Test, Fisher's Exact, Linear Trend and Poisson Regression. Of the 597 women interviewed, 12% had this disorder. Those without a partner had 10% more prevalence of alcohol use disorder than those with a partner; smokers had 25% more than non-smokers, while those diagnosed with systemic arterial hypertension had 5% less than non-hypertensive. The research indicated a high prevalence of alcohol use disorder, which indicates that health policies need to pay attention to this theme, especially for single women, smokers and hypertensive patients, who were the most compromised in this study.